Differentiation of Audit Quality Between Big 4 and Non-Big 4 Auditors (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the differences in audit quality between Big 4 and Non-Big 4 auditors in Indonesia, focusing on property and real estate companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The research sample was selected using a purposive sampling method based on certain criteria, such as the availability of audited financial statements and the consistency of auditor use. The total sample consisted of 100 companies, 50 audited by Big 4 auditors and 50 by Non-Big 4 auditors. Over a three-year period, 300 financial statements were collected as observation units. To examine the differences in audit quality between the two groups of auditors, a t-test method was used on three main indicators: audit opinion, audit report lag, and discretionary accruals. The results show that Big 4 auditors tend to provide firmer audit opinions and complete audits more efficiently. However, no consistent differences were found between Big 4 and Non-Big 4 auditors in suppressing earnings management practices. These findings indicate that audit quality is influenced not only by auditor size, but also by institutional factors, independence, and the effectiveness of regulatory oversight. This research provides empirical contributions for regulators, investors, and management in considering auditor selection, as well as expanding the literature on auditing in the property and real estate sector in developing countries.